2006
DOI: 10.1128/aac.50.3.1086-1088.2006
|View full text |Cite
|
Sign up to set email alerts
|

Activities of Telithromycin, Erythromycin, Fluoroquinolones, and Doxycycline against Campylobacter Strains Isolated from Finnish Subjects

Abstract: The in vitro susceptibilities of 478 Campylobacter jejuni and Campylobacter coli strains isolated from Finnish subjects during 2002 to 2004 were determined. Susceptibility to erythromycin remained high, and telithromycin did not offer any advantage over erythromycin. Reduced susceptibilities to fluoroquinolones and doxycycline were detected almost exclusively among isolates of foreign origin.Campylobacter jejuni and C. coli are the most frequent bacterial enteropathogens in many countries, such as Finland (14)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 18 publications
3
11
0
2
Order By: Relevance
“…This finding is consistent with data from previous studies showing that the C. coli strains are macrolide resistant more often than C. jejuni strains (8,23). Because of the increasing trend of resistance among Campylobacter spp., routine susceptibility testing is an important tool to choose an appropriate antimicrobial treatment for the patient.…”
Section: Discussionsupporting
confidence: 83%
“…This finding is consistent with data from previous studies showing that the C. coli strains are macrolide resistant more often than C. jejuni strains (8,23). Because of the increasing trend of resistance among Campylobacter spp., routine susceptibility testing is an important tool to choose an appropriate antimicrobial treatment for the patient.…”
Section: Discussionsupporting
confidence: 83%
“…In some of those studies, the results have been in line, though in some other studies, inconsistencies between the methods have been observed (8,9,15,(17)(18)(19)(20). Nevertheless, the disk diffusion test is currently widely used, since it is easy to perform in clinical microbiology laboratories.…”
supporting
confidence: 57%
“…Several previous papers have focused on the efficacy and accuracy of the disk diffusion method and the Etest method compared to the agar plate dilution or broth microdilution methods, with somewhat contradictory results (8,9,15,17,19,20). In these studies, the disk diffusion tests were performed only once for each strain.…”
Section: Discussionmentioning
confidence: 99%
“…Birçok ülkede yapılan çalışmalarda gastroenterit etiyolojisinde C.jejuni başta olmak üzere kampilobakterlerin en sık rastlanan etken olduğu vurgulanmaktadır 4,[19][20][21][22][23] . Hamidian ve arkadaşlarının 19 İran'da yaptıkları çalışmada, ishalli hastaların %8.7 (49/562)'sinden Campylobacter spp.…”
Section: Moleküler Analizunclassified